N-Tupled Coincidence Point Theorems in Partially Ordered Metric Spaces for Compatible Mappings. (12th March 2014) - Dalal, Sumitra; Khan, Muhammad Alamgir; Chauhan, Sunny
Abstract : The intent of this paper is to introduce the notion of compatible mappings for n -tupled coincidence points due to (Imdad et al. (2013)). Related examples are also given to support our main results. Our results are the generalizations of the results of (Gnana Bhaskar and Lakshmikantham (2006), Lakshmikantham and Ćirić (2009), Choudhury and Kundu (2010), and Choudhary et al. (2013)).